2020
DOI: 10.3329/bjms.v19i4.46632
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hypertension prevention as an actual medical and social problem

Abstract: Social changes, technological re-equipment, intensive formation of urban infrastructure have led to a constant increase in stress factors and an excessive growth of the nervous and psychological population burden. As a result of these processes in economically developed countries, acute diseases are becoming less and less significant, unlike the group of chronic disorders, such as arterial hypertension. Data from the review of the literature and the data we have received indicate that there is an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
6
0
5
Order By: Relevance
“…Not surprisingly, we found that hyperuricemia was more commonly diagnosed compared with other CKD causes in the PD patients with diabetes. Diabetes, as well as hypertension, has been recognized as a risk of GFR decline in CKD patients [13][14][15]20,22]. In agreement with our result, the presence of diabetes in predicting RRF decline in PD patients has been also demonstrated in previous studies [9,10,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Not surprisingly, we found that hyperuricemia was more commonly diagnosed compared with other CKD causes in the PD patients with diabetes. Diabetes, as well as hypertension, has been recognized as a risk of GFR decline in CKD patients [13][14][15]20,22]. In agreement with our result, the presence of diabetes in predicting RRF decline in PD patients has been also demonstrated in previous studies [9,10,21].…”
Section: Discussionsupporting
confidence: 92%
“…The term RRF is generally understood to mean the residual capacity of the kidneys to eliminate water and uremic toxins [5,19]. It plays a significant role in maintaining fluid balance and, accordingly, blood pressure, phosphorus control, nutrition and toxins removal [4,5,19,20]. However, an optimal method for measuring RRF has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…-виявлено більш високі рівні вмісту лептину серед (81,1±5,4) % пацієнтів із пССР та достовірно (р<0,01) менш часто в групі з нССР -серед ( Проблема виявлення молодих людей з артеріальною гіпертензією на ранньому етапі, стратифікація серцево-судинного ризику, індивідуальний підбір адекватної терапії, а також упровадження профілактичних заходів щодо найпоширеніших факторів серцево-судинного ризику (ССР), у тому числі ожиріння на етапі первинної ланки медичної допомоги залишається дискутабельним та потребує подальшого вивчення [3,4,7].…”
Section: оригінальні дослідженняunclassified
“…Loss of kidney function decreases renal oxalate clearance and increases plasma oxalic acid (POx) concentration, according to the progression of chronic kidney disease (CKD) stages (Robijn et al, 2011;Perinpam et al, 2017). The accumulation of oxalate may be associated with oxidative stress, inflammation (Khan, 2014;Ermer et al, 2016;Dominguez-Gutierrez et al, 2018;Korol et al, 2021) and a high risk of cardiovascular disease (CVD) (Liu et al, 2014;Fan X et al, 2017;Arafa et al, 2020;Demikhov et al, 2020) in patients with kidney stones. However, although impaired oxalate homeostasis is a well-known occurrence in patients with end-stage renal disease (ESRD), a high POx concentration has never been considered a trigger for oxidative stress, systemic inflammation, and CVD risk in these patients.…”
Section: Introductionmentioning
confidence: 99%